Pemanfaatan Digital Marketing sebagai Media Pemasaran Tenun Ulos di Desa Sigaol Timur - Krismanto Erick Tobush Naibaho; Gloria J.M Sianipar (Universitas 45 Surabaya, 2025)
East Sigaol Village is one of many villages that produce Ulos Weaving in Toba Regency which still carries out product marketing activities using a traditional system, this is still done not because the ulos weaving actors reject Digital Marketign but do not understand in utilizing and maximizing the use of Digital Marketing. The purpose of the activities carried out by providing training and assistance on understanding the right Digital Marketing from various existing options as a means that can later be used for MSME players in marketing ulos weaving products that are more attractive, innovative, informative, and professional. The methods used in this service activity are observation, implementation of activities and evaluation and monitoring. In this PKM activity, the enthusiasm of MSME actor participants was very large to know, understand and practice the use of Instagram and Tiktok as a means of online marketing. Where the results of this activity are expected to show a positive and significant increase in the knowledge of participants and MSME players regarding Instagram and TikTok which can be used as marketing media.